Police Referral Practices and Social Service Agency Practices in Three Metropolitan Areas, 1977 - Ostrom, Elinor ([Verlag nicht ermittelbar], 1984)
The dataset contains two related studies conducted in the metropolitan areas of St. Louis, Missouri, Tampa - St. Petersburg, Florida, and Rochester, New York. The study of police referral practices provies information on the types of calls made to police departments, the referrals made to social service agencies from these calls, and the pattern of citizen demands. Data for this study were collected from 26,465 calls for police service at 21 police departments. The 36 variables include the nature of the call, characteristics of the caller, and the type of agency receiving the referral.